Faktor-Faktor yang memengaruhi Nilai Perusahaan Manufaktur di BEI - Metta Laela Sari; Apit Susanti (Media Bisnis, 2021)
The purpose of this research is to obtain empirical evidence from the influence of independent variables including, company size, company age, capital structure, financial performance, profitability, and current ratio on dependent variable firm value. Population in this research are manufacturing companies that are listed in Indonesia Stock Exchange from 2018 to 2020. The method that is used to select the research samples is a purposive sampling method. By using this method, 77 companies fulfill the criteria that has been set before. The results show that there are 231 data that can be used as a research sample. Then, this research used multiple regression methods to analyze the data. The results of this study prove that company age, financial performance profitability, and current ratio have influence toward firm value. If company age and profitability are increasing, firm value will decrease, however if financial performance and liquidity are increasing, the firm value will also increase. However, company size and capital structure have no impact on firm value.